2005
DOI: 10.1128/jcm.43.9.4751-4757.2005
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Analysis of Staphylococcus epidermidis Isolates Carrying or Lacking Biofilm-Mediating Genes by Multilocus Sequence Typing

Abstract: Staphylococcus epidermidis is part of the normal microflora of the human skin but is also a leading cause of device-associated infections in critically ill patients. Commensal and clinical S. epidermidis isolates differ in their ability to form biofilms on medical devices; the synthesis of biofilms is mediated by the icaADBC operon. Currently, the epidemiological relatedness between ica-positive and -negative isolates is not known; neither is it known whether the ica genes can spread to biofilm-negative strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 36 publications
6
122
0
1
Order By: Relevance
“…Strains with IS256 integrated into ica and agr genes have been isolated from infection (Kozitskaya et al 2004;Vuong et al 2004b). In addition, the presence of IS256 appears to be correlated with the invasiveness of S. epidermidis strains (Gu et al 2005;Kozitskaya et al 2005). However, although IS256 might have a genuine role in the adaptation of the bacterial population to a different ecological niche, and thus to bacterial versatility, one can probably not call it a true regulator.…”
Section: Regulation Of Exopolysaccharide (Pia) Synthesismentioning
confidence: 96%
“…Strains with IS256 integrated into ica and agr genes have been isolated from infection (Kozitskaya et al 2004;Vuong et al 2004b). In addition, the presence of IS256 appears to be correlated with the invasiveness of S. epidermidis strains (Gu et al 2005;Kozitskaya et al 2005). However, although IS256 might have a genuine role in the adaptation of the bacterial population to a different ecological niche, and thus to bacterial versatility, one can probably not call it a true regulator.…”
Section: Regulation Of Exopolysaccharide (Pia) Synthesismentioning
confidence: 96%
“…S. epidermidis possesses superb recombination potential and the ability to transfer genetic material, resulting in the spread and evolution of resistance traits within nosocomial bacterial communities (Ziebuhr et al 2006). The evolving nature of S. epidermidis and its adaptation to the dynamic nosocomial environment has recently been highlighted by Kozitskaya et al (2005) who reported that S. epidermidis infections were mainly caused by a single intercellular adhesin (ica)-positive clone of S. epidermidis (Sequence type 27) whose presence was widespread within hospital settings in Germany. The ST27 clone was rarely found outside medical facilities and differed from commensal strains in the community and it was hypothesised that the successful establishment of ST27 within nosocomial environments was facilitated by the presence of genes encoding biofilms and resistance traits.…”
Section: Persister Cellsmentioning
confidence: 99%
“…Kozitskaya et al [27] sequenced S. epidermidis isolates which were collected from German, Irish, Norwegian, and North American population. ST27 was the dominant sequence type they identifi ed, followed by ST2 and sporadically ST5.…”
Section: Multilocus Sequence Typingmentioning
confidence: 99%
“…SCCmec types I to IV were determined by a multiplex PCR with specifi c primers and subseque nt visualization of the amplifi ed DNA fragment patterns by agarose gel electrophoresis as described by Oliveira et al [26] and Kozitskaya et al [27].…”
Section: Determination Of Sccmec Typesmentioning
confidence: 99%